Urban brownfields to gardens : minimizing human exposure to lead and arsenic - Defoe, Phillip Peterson (Kansas State University, 2014)
Urban gardens have been a popular re-use option in the transformation of brownfields—located in older industrialized cities and near peri-urban developments. They provide accessible, available, and affordable supplies of fresh fruits and vegetables, effectively reducing the enigma of “food deserts” across U.S. cities. However, direct (soil ingestion, inhalation) and indirect (soil-plant-human) human exposure concerns about real or perceived trace element contamination in urban soils persist due to previous use. Elevated lead (Pb) and/or arsenic (As) concentrations were found at two (Tacoma and Seattle, WA) urban gardens. The Tacoma site was contaminated with Pb (51 to 312 mg kg-1) and As (39 to 146 mg kg-1), whereas soil Pb at the Seattle site ranged from 506 to 2,022 mg kg-1, and As concentrations were < 20 mg kg-1. Experimental design at both sites was a randomized complete block with a split-plot arrangement (main plots: biosolids/compost vs. non-amended control; sub-plot: plant type). Tacoma site treatment included a Class A biosolids mix (TAGRO) with dolomite. The Seattle site was amended with Cedar-Grove Compost (CGC) plus dolomite. Efficacy of biosolids/compost amendment in reducing Pb and As concentrations was evaluated using root, leafy, and fruit vegetables. Soil Pb and As bioaccessibility were also evaluated. Food chain transfer of Pb and As in vegetables due to surface contamination of produce samples were evaluated on the basis of cleaning procedures. A laboratory incubation study and a controlled greenhouse experiment were conducted on soils collected from the Tacoma site. Effectiveness of addition of laboratory synthesized ferrihydrite (Fh: iron oxyhydroxide) and TAGRO mix, each alone or in combination were screened and tested on the Pb and As co-contaminated Tacoma soil. Extended X-ray Absorption Fine Structure (EXAFS) spectroscopy studies of Pb and As were conducted on incubation study samples to understand treatment-induced Pb- and As-speciation changes. Dilution of soil Pb (10 to 23%) and As (12 to 25%) were observed for biosolids amendment at the Tacoma site, while CGC amendment resulted in 20 to 50% dilution in soil Pb at the Seattle site. Biosolids and CGC amendments reduced Pb concentrations in the vegetables by 50% to 71%. At both sites, Pb concentrations of root vegetables exceeded the MLs established by the Food and Agriculture Organization (FAO) and the World Health Organization (WHO). Arsenic concentrations in vegetables were below an estimated ML and were reduced by 46% to 80% when grown on biosolids amended soils. Laboratory cleaning further reduced Pb and As food-chain transfer in vegetables grown in contaminated urban soils. Laboratory incubation and greenhouse studies showed dissolution of Pb in TAGRO plus Fh, and Pb concentrations in Fh amendments were significantly lower than the other amendments. Bioaccessible Pb and As were low. Significant reductions in bioaccessible As were observed when soils were amended with both TAGRO and Fh. X-ray absorption spectroscopy results indicated that chloropyromorphite-like (stable Pb phosphates) phases were the most dominant Pb species. Arsenic existed mainly as As5+, scorodite (FeAsO4•2H2O)-like species in all the treatments ranging from about 60% (control) to about 70% (TAGRO plus ferrihydrite). Amendments utilizing both biosolids and Fh significantly reduce human exposure risks present in urban soils contaminated with Pb and As.
Keywords: Environmental science; Brownfields; Bioavailability; Lead; Arsenic; Urban soils; Agronomy (0285); Environmental Sciences (0768)